Effects of sodium phosphate and caffeine loading on repeated-sprint ability - Buck, C.; Guelfi, K.; Dawson, B.; McNaughton, L.; Wallman, K. (Journal of Sports Sciences, 2015)
The effects of sodium phosphate and caffeine supplementation were assessed on repeated-sprint ability. Using a randomised, double-blind, Latin-square design, 12 female, team-sport players participated in four trials: (1) sodium phosphate and caffeine, (2) sodium phosphate and placebo (for caffeine), (3) caffeine and placebo (for sodium phosphate) and (4) placebo (for sodium phosphate and caffeine), with ~21 days separating each trial. After each trial, participants performed a simulated team-game circuit (4 × 15 min quarters) with 6 × 20-m repeated-sprints performed once before (Set 1), at half-time (Set 2), and after end (Set 3). Total sprint times were faster after sodium phosphate and caffeine supplementation compared with placebo (Set 1: P = 0.003; Set 2: d = -0.51; Set 3: P < 0.001; overall: P = 0.020), caffeine (Set 3: P = 0.004; overall: P = 0.033) and sodium phosphate (Set 3: d = -0.67). Furthermore, total sprint times were faster after sodium phosphate supplementation compared with placebo (Set 1: d = -0.52; Set 3: d = -0.58). Best sprint results were faster after sodium phosphate and caffeine supplementation compared with placebo (Set 3: P = 0.007, d = -0.90) and caffeine (Set 3: P = 0.024, d = -0.73). Best sprint times were also faster after sodium phosphate supplementation compared with placebo (d = -0.54 to -0.61 for all sets). Sodium phosphate and combined sodium phosphate and caffeine loading improved repeated-sprint ability.